Isolation, Characterization and Biological Activities of Chemical Constituents of Ophiorrhiza and Hedyotis Species - Hamzah, Ahmad Sazali (1994)
Chemical investigation on the leaves of Ophiorrhiza species, O. communis and O. tomentosa, has resulted in the isolation of two indole type alkaloids, harman and strictosidinic acid. Strictosidinic acid was isolated from the butanol extract of both Ophiorrhiza communis and O. tomentosa while harman was isolated from O. communis only. The structures of these alkaloids were elucidated using modern spectroscopic techniques such as UV, IR, NMR, MS and also by comparison with the literature. A study on the constituents of Hedyotis verticil lata has resulted in the isolation of kaempferitrin and Hv2 whereas from Hedyotis herbacea, kaempferol-3-0-rutinoside, ursolic acid, kaempferol-3-0-arabinopyranoside and quercetin galactoside were isolated. These structures were determined using modern spectroscopic techniques and also by comparison with the literature. A bioassay was also carried out using brine shrimp and anti bacterial tests on the pure and crude compounds. The brine shrimp tests showed that some of the compounds were very toxic whereas the anti-bacterial tests showed that some compounds have anti-bacterial properties and certainly these compounds have potential for further investigations for their medicinal and practical uses.